AN INTERACTIVE BOOK TO PROMOTE EMPATHY IN EARLY CHILDHOOD TOWARD SOUTH KALIMANTAN'S ENDEMIC WILDLIFE - Fadilla, Raisa; Chandra, Noor Eka; Listia, Rina; Febriyanti, Emma Rosana; Hidayat, Fahmi; Reyhan, Muhammad; Aditya, Muhammad Rifki (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2024)
This research aims to develop an interactive book as a medium to foster empathy in early childhood towards endemic animals in South Kalimantan, particularly the proboscis monkey (Bekantan) and mudskipper fish (Timpakul). The research follows a research and development (R&D) methodology, encompassing need analysis, product design, development, and evaluation stages. The interactive book, titled Antan & Kepi: The Friendship that Grew by the River, tells the story of a friendship between Antan, the proboscis monkey, and Kepi, the mudskipper, which forms when Antan shows empathy by rescuing Kepi from being trapped in rocks. The book aims to address the identified lack of local wisdom-based reading materials, particularly those featuring endemic animals, available to young learners in South Kalimantan. The product was validated by two experts: a media expert and an early childhood English expert. The validation process assessed content feasibility, alignment with psychological and linguistic development, and technical aspects of media presentation. The final product received an overall validation score of 86.08%, indicating high feasibility for use. Despite this, experts suggested improvements in font size and image clarity to enhance readability and visual appeal. The findings highlight the potential of interactive media to contextualize learning and support language acquisition while instilling empathy and environmental awareness in young children. The interactive book provides an engaging, culturally relevant resource for early childhood education, offering a meaningful, localized learning experience that connects children with their environment.